The Effect of Liquidity, Activity, Capital Structure, Profitability on Sustainable Growth and Company Value with Good Corporate Governance as a Moderating Variable in Heavy Construction and Civil Engineering Sub-Sector Companies Listed on the Indonesia St - Nur Rahmad Alfin Mustaqim; Tri Ratnawati; Ida Ayu Sri Brahmayanti (Global Economics: International Journal of Economic, Social and Development Sciences, 2025)
This study investigates the effects of liquidity, activity, capital structure, and profitability on sustainable growth and firm value in heavy construction and civil engineering companies listed on the Indonesia Stock Exchange. Using data from 18 companies (2021–2023) and applying SEM-PLS analysis, results show that activity and profitability positively and significantly influence sustainable growth, while liquidity and capital structure do not. Sustainable growth significantly mediates the impact of activity on firm value but does not mediate the effects of capital structure or profitability. The study suggests that effective management of operational activities and profitability supports sustainable growth, which in turn enhances firm value. These findings offer insights for managers and investors to focus on sustainable growth strategies for long-term value creation in the Indonesian construction sector.